Dynamic scheduling of precast element installation by probabilistic approach & IFC exchange behavior study for interoperability in BIM software - Shah, Vishal Snehal (2019)
Construction processes are stochastic in nature. Therefore, deterministic analysis of construction processes fails to incorporate uncertainty in scheduling models of construction operations. This project focusses on using probabilistic approach to account for the uncertainty and develop models that provide realistic estimates of construction processes. This project will develop a system that uses probabilistic approach for dynamic scheduling of precast element installation. The system will include integration of remote databases and predictive analytics tools, and it will be tested on a real construction operation of precast element installation to provide the best time estimates of processes involved in this operation. The best time estimates will be displayed on a BIM software with the help of a plugin developed on the software. Each BIM software has their own issues in importing IFC files into its platform. No matter how good other software can export IFC, something will be changed or lost once it is brought into another software. This project focusses on IFC exchange behavior between two BIM software namely Revit and Tekla. This project will include interoperability IFC tests that will cover simple elements transfer, multiple elements transfer and their interaction, and finally complex real HDB model. Based on these tests, solutions utilizing current settings available in the BIM software will be proposed to achieve semantic level interoperability. Finally, user guide will be prepared that will compile all the possible workarounds that will help achieve maximum semantic level interoperability for IFC transfers between BIM software.